Assumptions For Building an Environmental Cost Account in An Energy Sector Company - Aleksandra FERENS (Communications of International Proceedings, 2021)
The complexity of the relations between the natural environment and the enterprise, which are a significant development barrier, involves accounting for social responsibility towards internal and internal stakeholders. The aim of the paper is to present the methods of measuring environmental costs and the assumptions for creating an environmental cost accounting model based on the pro-ecological value chain built up for an energy sector company.  The information system of the energy sector company was investigated in order to identify the links with the natural environment, which are characterized by environmental costs. For this purpose, the concept of a value chain based on the organizational structure of the audited entity was used.The results of the analysis made it possible to build an ecological value chain of the energy sector company and to specify the environmental processes and activities. The original concept, scope and taxonomy of environmental costs were also proposed to provide the backbone for building an environmental cost accounting model. Originality: The paper builds upon research results in the field of creating environmental cost accounting, pinpointing the gaps related to the identification of environmental costs in the current information systems of enterprises, and confirms the need to improve the content of business management reports with quantitative and qualitative information in this regard.
Keywords: Environmental Costs; Environmental Cost Accounting; Sustainable And Continuous Development